2012
DOI: 10.1104/pp.112.203968
|View full text |Cite
|
Sign up to set email alerts
|

Genomics and Localization of the Arabidopsis DHHC-Cysteine-Rich Domain S-Acyltransferase Protein Family    

Abstract: Protein lipid modification of cysteine residues, referred to as S-palmitoylation or S-acylation, is an important secondary and reversible modification that regulates membrane association, trafficking, and function of target proteins. This enzymatic reaction is mediated by protein S-acyl transferases (PATs). Here, the phylogeny, genomic organization, protein topology, expression, and localization pattern of the 24 PAT family members from Arabidopsis (Arabidopsis thaliana) is described. Most PATs are expressed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
132
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(138 citation statements)
references
References 70 publications
6
132
0
Order By: Relevance
“…This resembles the Ras2p pathway of yeast (Linder and Deschenes, 2007). Similar to animals, there are 24 predicted PATs in plants (Hemsley et al, 2005;Batistic, 2012), and it is known that each of them displays a specific intracellular localization to the various membrane compartments of the cells with most proteins localized to the PM. It is remarkable that among the pool of cotranslationally predicted MYRed proteins shown recently to undergo PAL, 97% of them display a Cys at either position 3 and/or 4 (80%) or 5 and 6 for the others (see Supplemental Table 9 in Hemsley et al, 2013), confirming as a result the annotation of predicted PALed proteins in the Arabidopsis myristoylome.…”
Section: Both Myr and Pal Usually Target A Protein To Defined Substrumentioning
confidence: 84%
See 1 more Smart Citation
“…This resembles the Ras2p pathway of yeast (Linder and Deschenes, 2007). Similar to animals, there are 24 predicted PATs in plants (Hemsley et al, 2005;Batistic, 2012), and it is known that each of them displays a specific intracellular localization to the various membrane compartments of the cells with most proteins localized to the PM. It is remarkable that among the pool of cotranslationally predicted MYRed proteins shown recently to undergo PAL, 97% of them display a Cys at either position 3 and/or 4 (80%) or 5 and 6 for the others (see Supplemental Table 9 in Hemsley et al, 2013), confirming as a result the annotation of predicted PALed proteins in the Arabidopsis myristoylome.…”
Section: Both Myr and Pal Usually Target A Protein To Defined Substrumentioning
confidence: 84%
“…In the case of CBLs, the occurrence and roles of the two acylations were clearly assigned. In Arabidopsis, PAL is ensured by 24 palmitoyl S-transferases (PATs), most of them being located at the PM (Batistic, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the repertoire of DHHCs in S. cerevisiae (Mitchell et al, 2006) includes seven enzymes, whereas T. brucei possesses 12 (Emmer et al, 2011) and Arabidopsis thaliana has 23 (Batistic, 2012), the same number as found in humans (Putilina et al, 1999). The P. falciparum genome encodes 12 DHHC-containing proteins, whereas T. gondii possesses the largest family in the Apicomplexa with 18 genes, 16 of which are expressed in the tachyzoite stage (Frenal et al, 2013).…”
Section: Enzymes Implicated In Protein Palmitoylationmentioning
confidence: 99%
“…PATs are transmembrane proteins containing 4-6 membrane spanning domains and possess highly variable N-and C-terminal cytosolic domains that are essential for their substrate specificity (Huang et al, 2009;Greaves et al, 2010;González Montoro et al, 2011;Howie et al, 2014). Different numbers of DHHC-CRD PATs have been found in various species, such as seven in yeast (Putilina et al, 1999), 23 in mammals (Fukata et al, 2006), and 24 in Arabidopsis (Hemsley and Grierson, 2008;Batistic, 2012).…”
mentioning
confidence: 99%
“…Analysis of the 24 Arabidopsis PATs shows that most of them have a broad and constant expression pattern at different developmental stages (Batistic, 2012). Transient expression of AtPAT-GFP in tobacco (Nicotiana benthamiana) showed that Arabidopsis PATs have very complex cellular membrane localization patterns where half of them reside in the plasma membrane and others in the endoplasmic reticulum, Golgi, vesicles, and tonoplast (Batistic, 2012), indicating that the plasma membrane is the main palmitoylation site in higher plants. This contrasts with mammals where the Golgi is the main site for the palmitoylation machinery (Ohno et al, 2006).…”
mentioning
confidence: 99%